Estudo de adsorção de tiofeno em carbono ativado - Rocha, Ana Vívian Parente (2010)
Concerns with environmental protection and human health have had a remarkable impact on vehicle emissions regulations. Following similar policies of governmental agencies worldwide, Brazilian Agência Nacional do Petróleo, Gás Natural e Biocombustíveis (ANP) has established a timetable for drastic reduction of sulfur content in diesel and gasoline in the last few years. Hydrodesulfurization (HDS) is the industrial process being currently employed for this matter. However, the HDS process is costly and, to achieve deeper desulfurization levels, it would require higher hydrogen pressure, which may eventually lead to the saturation of olefinic compounds, causing a decrease in gasoline octane number. Therefore, special attention has been given to the use of adsorption for additional removal of sulfur compounds from effluent streams of existing hydrotreatment (HDT) plants. Adsorption processes may operate under mild temperature and pressure conditions. In the present work, desulfurization in thiophene/n-hexane, thiophene/n-octane and thiophene/toluene/n-octane mixtures were conducted, together with a study of thiophene/toluene selectivity, all experiments using activated carbon 830 W by Norit (Netherlands) as sorbent. The adsorbent was characterized texturally by adsorption/desorption of N2 at 77 K and results showed it to be a microporous material. Adsorption of thiophene from n-hexane solutions and thiophene/toluene selectivity were carried out using the experimental technique of headspace chromatography finite bath. Adsorption isotherms thus obtained showed unfavorable behavior and the adsorbent selectively adsorbs toluene as compared to thiophene, reaching maximum selectivity on liquid/solid ratio of less than 4%. Adsorption of thiophene in n-octane and n-octane/toluene (4:1 vol.) was assessed by fixed bed experiments performed under a flow rate of 0.5 mL/min, two different temperatures and sulfur concentration in the feed ranging from 275 to 1000 ppm. Adsorption isotherms thus measured fall within the Henry’s Law region (linear) with dimensionless adsorption constants of 3.7 and 3.0 at 30 ºC and 45 ºC, respectively. For the feed concentration of 1000 ppm in n-octane, the measured dynamic adsorption capacity was 0.035 mmolS/gads, which was reduced to 0.020 mmolS/gads when toluene was present. Regardless the inlet sulfur concentration, the amount of adsorbed thiophene decreased considerably in the presence of the aromatic compound. Breakthrough curves of thiophene in n-octane were simulated according to a mathematical model that assumed axially dispersed flow and mass transfer described by a linear driving force approximation (LDF). The model was solved numerically by orthogonal collocation in finite elements, using the commercial solver gPROMS. The proposed model matched experimental data reasonably well, especially for the feed concentration of 1000 ppm. The LDF time constant was the tunable parameter between simulations and experimental data and the best average values were found to be 3.3 and 2.2 min-1 at 30 and 45 ºC, respectively.